A Cross-sectional Analysis of the Prevalence of Barrett’s Esophagus in Otolaryngology Patients with Laryngeal Symptoms - Nason, Katie S. (2013)
BACKGROUND: Populations at risk for esophageal adenocarcinoma remain poorly defined. Laryngeal symptoms can be secondary to laryngopharyngeal reflux (LPR) and can occur without associated gastroesophageal reflux symptoms such as heartburn and regurgitation. GOAL: We sought to determine the prevalence of Barrett’s esophagus (BE) in otolaryngology patients with laryngeal symptoms ± typical GERD symptoms. STUDY: We performed a cross-sectional study of otolaryngology clinic patients who reported laryngeal symptoms. Symptoms, medications and exposure histories were obtained. Unsedated transnasal endoscopy was performed. Suspected BE was biopsied and confirmed histologically. Risk factors and prevalence of BE were assessed. RESULTS: Two hundred and ninety five patients were enrolled (73% male, median age 60 [IQR 51–68]). The overall prevalence of BE was 11.8% (n=33). Antisecretory medication use was present in 56% (n=156) of patients at enrollment. Compared to patients without BE, patients with BE were more likely to be male (p=0.01) and to report occupational lung injury (p=0.001). Duration, but not severity of laryngeal symptoms, significantly increased the odds of Barrett’s esophagus (OR 5.64 [95% CI 1.28, 24.83] for a duration of symptoms > 5 years). Of patients with BE, 58% (n=19) had co-existing LPR and GERD symptoms and 30% (n=10) had only LPR symptoms. Presence and size of hiatal hernia and length of columnar lined esophagus were significant risk factors for BE. CONCLUSIONS: Long-standing laryngeal symptoms are associated with the presence of BE in otolaryngology patients. Patients with chronic laryngeal symptoms and no identifiable ear, nose, or throat etiology for those symptoms may benefit from endoscopic screening regardless of whether typical GERD symptoms are present.